Skew detection and correction of mushaf Al-Quran script using hough transform - Bafjaish, Salem Saleh; Azmi, Mohd Sanusi; Al-Mhiqani, Mohammed Nasser; Radzid, Amirul Ramzani; Mahdin, Hairulnizam (The Science and Information (SAI) Organization Limited, 2018)
Document skew detection and correction is mainly one of base preprocessing steps in the document analysis. Correction of the skewed scanned images is critical because it has a direct impact on image quality. In this paper, the authors proposed a method for skew detection and correction for Mushaf Al-Quran image pages based on Hough transform method. The technique uses Hough transform lines detection for calculating the skew angulation. It works for different version of Mushaf AlQuran image pages which has skewed text zones. Moreover, it can detect and correct the skew angle in the range between 20 degrees. Experiment conducted on different Mushaf Al-Quran image pages shows the accuracy of the method.